The effect of the gold index and NIKKEI on the Indonesian market index - Dina S. Gerung; Silva S. Arikalang; Tessalonika Agow; Irmando M. J. J. Sambeka (The Contrarian : Finance, Accounting, and Business Research, 2022)
Gold and NIKKEI are two important market mechanisms and can directly affect the market in Indonesia. The Covid-19 pandemic has had an adverse impact on the world economy and one of them is Indonesia. This study observes the period from June 2021 to May 2022. This study finds that in the period June to December 2021 the gold index is negative and significant on the JCI although NIKKEI has quite a positive effect. Reversely, in the period of January to May 2022, the gold index has a positive effect on the JCI movement, but not on NIKKEI.